THE CORRELATION BETWEEN STUDENTS’ VOCABULARY MASTERY AND THEIR SPEAKING ABILITY AT EIGHT-GRADE STUDENTS OF SMPN 1 PRINGGABAYA ACADEMIC YEAR 2022/2023 - Makmur Hadi; Sahuddin; Lalu Jaswadi Putera (Program Studi Pendidikan Bahasa Inggris, 2023)
For the academic year 2022–2023, this study aims to know the correlation between speaking ability a and vocabulary mastery at the eighth graders of SMPN 1 Pringgabaya's vocabulary and speaking proficiency. This study used quantitative methodologies and samples from as many as eleven classes in class VIII, with a representative from each class. The duration of this study was roughly six weeks. 33 students took multiple choice vocabulary examinations with up to 25 questions, and within 5 weeks, speaking assessments were given to the students. In addition, the average score for male vocabulary mastery was 58 and the average score for speking mastery female was 67.33. The average vocabulary mastery score for male was 63.33, and the average score for female speaking ability was 66.11. It can be said that there is no correlation between the 8th students at SMPN 1 Pringgabaya's vocabulary proficiency and their speaking skills. As a result, the alternative hypothesis (Ha) is disproved while the null hypothesis (Ho) is accepted. This indicates that the hypothesis assumption's correlation value is less than the significant value (Rxy rt).